Ionospheric photoelectrons: A lateral thinking approach - Richards, P. G. (Frontiers in Astronomy and Space Sciences, 2022)
This paper presents a personal account of developments in the solution of two related problems that limited the accuracy of ionosphere calculations in the 1980s. The first problem concerns the model-data discrepancies in the ionosphere photoelectron flux spectrum. Early comparisons between measured and modeled data revealed discrepancies in magnitude and shape. A lateral thinking approach revealed that there were problems with two key photoelectron model inputs: namely, the electron impact cross-sections and the solar extreme ultraviolet irradiance. This work led to the development of a widely used EUVAC solar irradiance model for ionosphere electron density calculations. The second problem relates to the neutral winds that are crucial for modeling variations in the ionosphere ion and electron densities. There is a lack of thermosphere neutral wind data because they are difficult to measure. The winds determine the altitude at which the electron density peaks. An accurate solution to this problem was the development of an algorithm that assimilates the altitude of the peak electron density into ionosphere models. This technique works because the altitude of the peak density is very sensitive to variations in the neutral wind.